Petty magic : being the memoirs and confessions of Miss Evelyn Harbinger, temptress and troublemaker - DeAngelis, Camille (New York : Crown Pub., 2010)
Using witchcraft to extend her considerable life, Evelyn Harbinger dons a youthful appearance to catch the eye of a man she believes to be the reincarnation of a beloved World War II espionage partner who lost his life helping her to advance the Allied cause.
Keywords: Older women -- Fiction; World War, 1939-1945 -- Veterans -- Fiction; Loss (Psychology) -- Fiction; Magic -- Fiction; Fantasy fiction; Love stories; Fantasy fiction; Love stories